Structured cobalt oxide catalysts for VOC abatement: the effect of preparation method - Topka, Pavel; Dvořáková, Michaela; Kšírová, Petra; Perekrestov, Roman; Čada, Martin; Balabánová, Jana; Koštejn, Martin; Jirátová, Květuše; Kovanda, František (Environmental science and pollution research international, 2020)
Magnetron sputtering was employed for the deposition of cobalt oxide thin films on stainless steel meshes. Catalysts prepared by sputtering in inert and oxidation atmosphere were compared with those obtained by electrochemical deposition and hydrothermal synthesis. Systematic characterization using X-ray diffraction, scanning electron microscopy, N 2 physisorption, infrared spectroscopy, Raman spectroscopy, and temperature-programmed reduction by hydrogen allowed detailed monitoring of their physicochemical properties. Ethanol gas-phase oxidation was employed as a model reaction to reveal the catalytic performance of the catalysts. It was shown that the catalyst prepared by magnetron sputtering in oxidation atmosphere exhibited the best mechanical stability among all studied catalysts. Moreover, its catalytic activity was 18 times higher than that of pelletized commercial cobalt oxide.